Equations- Factorization of a polynomial equation – Exercise 5604

Exercise

Factor the polynomial equation

x43x24=0x^4-3x^2-4=0

Final Answer


(x2)(x+2)(x2+1)=0(x-2)(x+2)(x^2+1)=0

Solution

First solution:

x43x24=0x^4-3x^2-4=0

To reach a quadratic equation, we define a new variable:

y=x2y=x^2

We set the new variable:

y23y4=0y^2-3y-4=0

We got a quadratic equation. Our equation coefficients are

a=1,b=3,c=4a=1, b=-3, c=-4

We solve it with the quadratic formula. Putting the coefficients in the formula gives us

y1,2=3±(3)241(4)21=y_{1,2}=\frac{3\pm \sqrt{{(-3)}^2-4\cdot 1\cdot (-4)}}{2\cdot 1}=

=3±252==\frac{3\pm \sqrt{25}}{2}=

=3±52=\frac{3\pm 5}{2}

Hence, we get the solutions:

y1=3+52=82=4y_1=\frac{3+ 5}{2}=\frac{8}{2}=4

y2=352=22=1y_2=\frac{3- 5}{2}=\frac{-2}{2}=-1

Thus, the factorizing of the quadratic equation is

y23y4=y^2-3y-4=

=(y4)(y+1)=(y-4)(y+1)

Going back to the original variable we get

=(x24)(x2+1)=(x^2-4)(x^2+1)

We break down the first factor using Short Multiplication Formulas (third formula) and get the factorizing

=(x2)(x+2)(x2+1)=(x-2)(x+2)(x^2+1)

Second solution:

x43x24=x^4-3x^2-4=

We express the second expression as sum and we get

=x44x2+x24==x^4-4x^2+x^2-4=

We extract a common factor from the first two expressions:

=x2(x24)+(x24)==x^2(x^2-4)+(x^2-4)=

Once again we extract a common factor – this time the expression in parentheses:

=(x24)(x2+1)==(x^2-4)(x^2+1)=

We break down the first factor using Short Multiplication Formulas (third formula) and get the factorizing:

=(x2)(x+2)(x2+1)=(x-2)(x+2)(x^2+1)

Have a question? Found a mistake? – Write a comment below!
Was it helpful? You can buy me a cup of coffee here, which will make me very happy and will help me upload more solutions! 

Share with Friends

Leave a Reply